HUBUNGAN PERSEPSI PERAWAT TENTANG SUPERVISI IPCLN DENGAN KEPATUHAN KEWASPADAAN STANDAR PENGGUNAAN APD DI RSUD dr. SOEKARDJO KOTA TASIKMALAYA - Asep Rahmadiana; Hilman Mulyana (Jurnal Skolastik Keperawatan, 2020)
ABSTRACT Introduction: IPCLN (Infection Prevention and Control Link Nurse) as the executor of the Infection Prevention and Control Program (PPI) in hospitals is required capable of performing their duties in monitoring compliance with standard precautions nurses. Important PPI implemented in hospitals to protect patients, staff, visitors, and families from the risk of transmission of infection. Purpose: To identify the relationship perception of nurses on adherence supervision IPCLN with the use of standard precautions Personal Protective Equipment (PPE) in RSUD dr. Soekardjo Tasikmalaya City. Methods: A quantitative research method descriptive design correlation and cross-sectional approach, the entire population of nurses from 16 inpatient units by the number of samples taken as many as 152 nurses, variable data retrieval perception about supervision of nurses by questionnaires and standard precautions for compliance with PPE use action observation. The research was conducted from May to June 2019 in RSUD dr. Soekardjo Tasikmalaya City. Analysis of the research data with nonparametric statistics and Mann Whitney test. Results: Nurses' perceptions of IPCLN supervision are at an average score of 73.11, so more than half of nursing nurses perceive supervision by IPCLN to be effective. The results of observations based on the standard precautions of using PPE for nurses with an average value of 65.86%. The relationship exists perception of nurses about the supervision of compliance with PPE use IPCLN with ρ- value 0,002 <alpha of 0.05. Discussion: These results indicate that the perception of nurses in implementing effective supervision be improved adherence to nursing standard precautions when performing nursing care actions. Management of the hospital need to increase socialization IPCLN understanding about the importance of the supervision of the nurses while giving care to resocialization IPCLN duties and functions as well as the implementation of reward and punishment.